2022
DOI: 10.1210/clinem/dgac735
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific Trajectories of Insulin Resistance Markers and Reduced Renal Function During 18 Years of Follow-up: TLGS

Abstract: Objective To investigate the association between the dynamic course of insulin resistance and chronic kidney disease (CKD). Methods In a longitudinal population-based Tehran Lipid and Glucose Study, 3071 eligible participants aged ≥20 years were followed for 18 years at three-year intervals. HOMA-IR and clinical surrogate markers of insulin resistance, including triglyceride-glucose index (TyG), visceral adiposity index (VAI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The Hanzhong Adolescent Hypertension Cohort study and our previous study found that the TyG index was independently associated with elevated arterial stiffness, which is an important predictor of CVD events [ 17 , 46 ]. In addition, the effects of TyG on diabetes, carotid atherosclerosis, hypertension, liver diseases, renal function and frailty have also been reported [ 47 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Hanzhong Adolescent Hypertension Cohort study and our previous study found that the TyG index was independently associated with elevated arterial stiffness, which is an important predictor of CVD events [ 17 , 46 ]. In addition, the effects of TyG on diabetes, carotid atherosclerosis, hypertension, liver diseases, renal function and frailty have also been reported [ 47 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Tehran Lipid and Glucose Study indicated that the TyG index can serve as an alternative marker to HOMA-IR and is associated with an increased risk of chronic renal disease and decreased renal function. 31 syndrome. 32,33 Since deteriorating renal function is a significant risk factor for poor prognosis in HF patients, with approximately 40% of HF patients experiencing renal impairment, 34 we hypothesize that there is also an association between the TyG index and patient prognosis in patients with acHF accompanied by RD.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that HOMA-IR exhibited a robust correlation with CKD in Korean adults, regardless of their T2DM status [ 7 ]. A comparable Iranian cohort study revealed that a one-unit increase in HOMA-IR was associated with a 72% and 37% increased risk of CKD in males and females, respectively [ 29 ]. In another study conducted among Chinese patients with MetS, a positive association was observed between HOMA-IR and the prevalence of CKD, but it was not statistically significant in females (male OR: 1.21, 95% CI 1.14–1.28, P ≤ 0.001; female OR: 1.01, 95% CI 0.99–1.02, P = 0.38) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%